Inbound Recruiting and its influence on resilience in applicants of the company W2 Asesores y Consultores - Tupayachi Cahuana, Winy (2021)
The objective of this article is to determine the influence of Inbound Recruiting on Resilience in applicants to the company W2 Asesores y Consultores. Inbound Recruiting is a new methodology for recruiting and selecting personnel that comes from Inbound Marketing, which is focused on the client, in this case, the candidates; who are mostly unemployed, therefore with negative effects in the personal and social sphere. In this sense, it is necessary to understand the direct influence that exists between these two concepts, Inbound Recruiting and Resilience, so that they can be replicated by various organizations. This study consisted of 314 applicants to operational processes, to whom the questionnaire adapted from Inbound Recruiting, and Resilience was applied. The scope of the research is descriptive-correlational. The results show that there is a moderate positive correlation (Rho = .449 **; p = .000), showing that the higher the Inbound Recruiting scores, the higher the Resilience scores.